Pengaruh Tingkat Kecukupan Modal (CAR), LDR, dan BOPO terhadap Profitabilitas - Guntur Cahyono (JMK (Jurnal Manajemen dan Kewirausahaan), 2018)
This study aims to examine the effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) and Operational Efficiency (BOPO) on Return on Assets (ROA) as a projection of the Financial Performance of Rural Banks for the period January 2014 to December 2016, Data used in this study were obtained from the quarterly Financial Report of PT. BPR Nusamba Ngunut Publication period January 2014 to December 2016 issued by Indonesian Bank. The results showed that the CAR variable had no effect on profitability with a significance level of 0.479> 0.05, and the LDR had no effect on profitability with a significance level of 0.935> 0.05, while BOPO had a negative and significant effect on ROA. The three significant variables, the BOPO variable has a negative and significant effect on ROA with a coefficient of 0.003. BPRs (issuers) are expected to pay more attention to efficiency levels to increase ROA on their financial performance.